Strategi Komunikasi Interaktif Ciewie Batik - Marsudi, Marsudi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2017)
To improve a company's positive image and reputation, Ciewie Batik attempts to develop interactive communication to consumers, both online and offline. This study discusses the strategies and forms of interactive communication that Ciewie Batik uses to run its business in an effort to penetrate domestic, national, and international markets. Using descriptive qualitative methods, this study has found that in order to maximize customer service and promotion, and in an effort to foster value from innovation, Ciewie Batik's interactive communication strategy is to integrate social media and Android applications and actively recruit web-resellers. For example by intensifying customer complaints and inquiries in an express manner. Additionally, by cons–tantly updating Ciewie Batik's website, increasing Facebook Fanpage, and actively recruiting web-reseller.